2007
DOI: 10.1016/j.pecs.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of electricity and hydrogen production systems with CO2 capture and storage—Part B: Chain analysis of promising CCS options

Abstract: Promising electricity and hydrogen production chains with CO 2 capture, transport and storage (CCS) and energy carrier transmission, distribution and end-use are analysed to assess (avoided) CO 2 emissions, energy production costs and CO 2 mitigation costs. For electricity chains, the performance is dominated by the impact of CO 2 capture, increasing electricity production costs with 10-40% up to 4.5-6.5 hct/kWh. CO 2 transport and storage in depleted gas fields or aquifers typically add another 0.1-1 hct/kWh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 26 publications
0
32
0
4
Order By: Relevance
“…As we want to compare the biomass value chains on a more general level, we exclude LUC induced GHG emissions from our analysis, but we consider this topic in our discussions. To calculate GHG abatement costs, we apply the methodology as described and used in Damen et al [31]: …”
Section: Avoided Ghg Emissions and Ghg Abatement Costsmentioning
confidence: 99%
“…As we want to compare the biomass value chains on a more general level, we exclude LUC induced GHG emissions from our analysis, but we consider this topic in our discussions. To calculate GHG abatement costs, we apply the methodology as described and used in Damen et al [31]: …”
Section: Avoided Ghg Emissions and Ghg Abatement Costsmentioning
confidence: 99%
“…This can also be assumed for the case of biogas since CO2 is already removed when biogas is upgraded to transport fuel quality. This can be compared to the CO2 capture cost linked to processes requiring an extra purification step like steel and iron, ammonia, refinery, cement, and fossil or biomass combustion plants estimated at 20€2015-170€2015/ ton CO2 in the short term (10-15 years) and 10€2015-100€2015/ton CO2 in the more long term (Damen et al, 2007;Finkenrath, 2011;Kuramochi et al, 2012Kuramochi et al, , 2013IEA, 2013). Even though it has been indicated that the cost for carbon capture represents a relatively modest share (a few percent) of the total electrofuel-production cost unless air capture is assumed (Graves et al, 2011;Tremel et al, 2015;Varone and Ferrari, 2015; see text footnote 1), using CO2 from biofuel production represent an attractive source for electrofuel production since more pure streams will likely be used first for economic reasons and the domestic biofuel actors, representing a considerable biofuel production capacity, in order to comply with sustainability requirements need to improve their production processes in terms of CO2 emissions.…”
Section: Methodsmentioning
confidence: 99%
“…In their review of the literature, Brynolf et al (see text footnote 1) also found that the cost of capturing CO2 generally is a minor factor in the total production cost of electrofuels representing less than 10% (when not considering CO2 capturing from air). CO2 can be captured from various industrial sources with costs ranging from about 10€2015 to 170€2015/ton CO2, depending on the CO2 concentration (Damen et al, 2006(Damen et al, , 2007Finkenrath, 2011;Goeppert et al, 2012;Kuramochi et al, 2012Kuramochi et al, , 2013IEA, 2013; see text footnote 1). This indicates that from an economic point Mohseni (2012), Grond et al (2013), Schiebahn et al (2015), and Tremel et al (2015).…”
Section: Electrofuel-production Efficiency and Costmentioning
confidence: 99%
“…The main contributor to overall cost of carbon capture and storage is the carbon capture process [86]. For the post-combustion technology, atmospheric-pressure absorbers and the solvent recycling attract higher capital cost compared to pre-combustion designs.…”
Section: Cost Of Electricity Outputmentioning
confidence: 99%
“…At present carbon capture technologies experience significant economies of scale, which means that they do not match well with decentralized energy supply, for example combined heat and power plants, or biomass power plants [86].…”
Section: Cost Of Electricity Outputmentioning
confidence: 99%